Synthesis, isolation and purification of [11C]-choline - Szydło, Marcin; Jadwiński, Michał; Chmura, Agnieszka; Gorczewski, Kamil; Sokół, Maria (Contemporary Oncology/Współczesna Onkologia, 2016)
[11C]-choline is an effective PET tracer used for imaging of neoplastic lesions and metastases of the prostate cancer. However, its production can be a challenge for manufacturers, as it has not yet been described in Polish or European pharmacopoeia. In this study the technical aspects of [11C]-choline production are described and detailed process parameters are provided. The quality control procedures for releasing [11C]-choline as solutio iniectabilis are also presented. The purity and quality of the radiopharmaceutical obtained according to the proposed method were find to be high enough to safely administrate the radiopharmaceutical to patients. Application of an automated synthesizer makes it possible to carry out the entire process of [11C]-choline production, isolation and purification within 20 minutes. It is crucial to maintain all aspects of the process as short as possible, since the decay half-time of carbon-11 is 20.4 minutes. The resulting radiopharmaceutical is sterile and pyrogen-free and of a high chemical, radiochemical, and radionuclide purity proved by chromatographic techniques. The yield of the process is up to 20%. [11C]-choline PET scanning can be used as accurate and effective diagnostic tool in all centers equipped with [11C]-target containing cyclotron.